Analisis Modal Intelektual pada Inovasi Sektor Pariwisata di Yogyakarta - Heri Susanto; Rosita Rosita; Rudi Prasetyo Ardi (ITB AAS INDONESIA, 2021)
An organization's ability to innovate depends on its intellectual capital. Our study attempts to examine the influence of individual components of intellectual capital on corporate innovation. This article proposes a method of classifying and measuring intellectual capital, highlighting the following three components. Human capital, organizational capital and social capital. Our goal is to explain a company's performance in the field of innovation and highlight the importance of each one Dimension of intellectual capital for a certain type of innovation (product, process, marketing and organization). For this purpose, a survey was carried out among 80 participating SMEs in the Yogyakarta tourist area. Company data was analyzed using SPSS using regression data analysis techniques through the developed hypothesis.